Living with environmental change in the endorheic oasis systems of the Northern Sahara - King, C (2011)
The oases of the northern Sahara illustrate the possibility that people and nature can work together to enhance life in a harsh and variable environment. This research investigates fifty years of experiences of living with environmental change in oasis systems, bringing together new data, archived environmental records and cultivators` observations. These are combined to gain insight into the environmental change processes, and the experiences gained by people through living with them in this regional context. Two detailed case studies deepen understanding of the socioeconomic dimensions and significance of these changes over the past two decades. The findings show how environmental changes constrained smallholders` traditional ecosystem management practices. Collective associations were weakened or disintegrated. National systems for environmental management and monitoring were overwhelmed. International recommendations for economic approaches to resource management and innovation to address water scarcity did not prove effective. On the other hand, instances where the international market transition appeared to be creating new opportunities for the restoration of common pool resource management were also identified. This investigation enabled a new perspective on the global dryland management debate to be generated in a context where research has most commonly been concentrated on national sectoral objectives for productivity and desert reclamation. Theoretical insights regarding the application of interdisciplinary research to understand environmental change, further research needs, and potential solutions are directly transferable to other regions where desiccation, salinization and groundwater degradation are accelerating due to climatic and global market-driven changes in land and water use.